2012
DOI: 10.1038/ejcn.2012.39
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the inequality of fruit and vegetable consumption between education levels indicated by the Korea National Health and Nutrition Examination Surveys

Abstract: ). The FV intakes were examined using 24-h dietary-recall surveys (n ¼ 35 725) and food frequency questionnaires (n ¼ 35 400). The relative index of inequality (RII) was used to examine the magnitude and trend of inequality in insufficient FV intake (o500 gram/day for total FV; o100 gram/day, less than once per day for fruits) between educational levels. RESULTS: The low-education group had lower intakes of total FV, vegetables excluding Kimchi and fruit (both by frequency and quantity), but higher intakes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Initiatives to increase the consumption of fruits and vegetables have been implemented in several developed countries, targeting different age groups (9,10) . However, the overall impact has been small and intake remains inadequate in many countries (11)(12)(13) . In developing countries, the prevalence of low fruit and vegetable consumption is even higher mainly due to barriers to access and affordability (14) and also due to characteristics of the stages of nutritional transition that countries are experiencing.…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives to increase the consumption of fruits and vegetables have been implemented in several developed countries, targeting different age groups (9,10) . However, the overall impact has been small and intake remains inadequate in many countries (11)(12)(13) . In developing countries, the prevalence of low fruit and vegetable consumption is even higher mainly due to barriers to access and affordability (14) and also due to characteristics of the stages of nutritional transition that countries are experiencing.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding kimchi consumption by educational level, subjects with < 12 years of education showed significantly decreased from kimchi consumption 1998 to 2012 (unadjusted P trend = 0.0012, Adjusted P trend = 0.0018). Hong et al [ 40 ] reported that kimchi intake by the low-educational group increased, whereas vegetable and fruit consumption except kimchi gradually decreased. Education may affect knowledge of good nutrition and appropriate food choices.…”
Section: Discussionmentioning
confidence: 99%
“…These data could reflect characteristics of the general Korean population. Studies on food intake based on KNHANES data have examined Korean dietary patterns [ 33 ], including consumption of rice and whole grains [ 34 35 ], eggs [ 36 ], beef and processed meat [ 37 38 ], ramen and noodles [ 39 ], and vegetables and fruit [ 14 40 41 42 ]. However, studies on average kimchi intake in the Korean population have never been performed other than to examine physicochemical, sensory, or preference characteristics using a convenient sampling method.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit and vegetables (F&V), milk, and dairy products are the main food sources for these nutrients. An increase in the proportion of individuals who do not meet the recommended criteria for F&V has been recently reported in the US [ 16 ], and a substantial portion of the Korean population did not meet the recommended criterion for F&V [ 17 ]. This may be responsible for the high prevalence of insufficient intake of micronutrients.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the dietary status of children and adolescents according to the socioeconomic status of their households, their parents’ smoking status, and their own eating behaviors. Indeed, it is possible that socioeconomic status, including parental education and household income, may influence food choices due to differences in nutrient-related knowledge, the priority accorded to health considerations, and the cost of food [ 5 , 8 , 17 , 18 ]. A study using the 2005 KNHANES data found that individual INQ values significantly differed according to paternal educational level, but this was not considered in the design of the KNHANES sampling method [ 12 ].…”
Section: Discussionmentioning
confidence: 99%